Urban spatial, engineering and management resilience capacity enhancement from a flood safety perspective - Junqi Li; Yue Zou; Jing Li; Shuai Si (Water-Energy Nexus)
The increasing frequency of extreme weather events caused by climate change has had a significant impact on cities worldwide. Resilient cities have become a prominent topic of discussion in both domestic and international urban planning. This paper examines the challenges and barriers faced in building resilient cities, as well as the current state of resilience construction in China amidst global flooding issues. By analyzing the impact factors of urban flooding, a comprehensive urban flood resilience evaluation model is proposed, comprising spatial resilience, engineering resilience, and management resilience. Previous studies have not closely integrated the influencing factors with the flood disaster process. The CRITIC assignment method takes into account the correlation between the indicators while objectively considering the magnitude of the differences between them. Therefore, this paper adopts the CRITIC assignment method to categorize and integrate the evaluating factors, aiming to enhance the overall resilience to urban floods. The flood resilience evaluation factors are reassessed in this study to ensure that the various systems and segments of the city can prevent, effectively respond to, and efficiently recover from flood disasters while achieving sustainable development.